Custom farming (service providing) system in paddy farming in Malaysian granary area - Man, Norsida (Faculty of Agriculture, Jember University, 2012)
Rice is an important food commodity in Malaysia and remains relevant to agriculture sector in Malaysia and this subsector is essential to ensure national food security. According to Muda Agriculture Development Authority (MADA) (2008), 90% of the farmers used modern mechanization and outsourcing their farm operations such as land preparation, seedling, planting, fertilizing, pest and diseases managing and harvesting. For these farm operations, the service for machinery and wage labor was provided by private service providers and Area Farmer Association (AFO). Custom hiring (Service Providing) System is really important due to the risen in the cropping intensity (Double Cropping System) and farm size (economic scale) in paddy farming in Muda granary area. However, how this custom farming system (Service Providing System) was established and the reason why they are still relevant until now was not yet identified. This study attempts to investigate the actual status of the service providing system (custom farming) in paddy farming in Muda area. This research focus on the role of service providers and the brokers as the middleman in service providing system that shows on how they cooperate and provide various services to farmers. Several aspects may influence the loyalty of farmer to the provider and broker such as reasonable rate of payment given by the provider and close relationship from generation to generation. However, there might be some ambiguity about the way of services performed by the provider and the broker. Therefore, by identifying any problems exist in this system, it will determine whether this system is effective or not. Subsequently, a better guideline or policies have to be created in order to improve the smoothness of the service providing system comparable with custom farming system in countries such as United Stated and Japan.